A Note on " The Balance of Payments and the Terms of Trade in Relation to Financial Controls" - Berglas, E.; Razin, A. (Review of Economic Studies, 1972)
Eitan Berglas, Assaf Razin; A Note on “ The Balance of Payments and the Terms of Trade in Relation to Financial Controls”12, The Review of Economic Studies, Vol